2017
DOI: 10.1093/jscr/rjx172
|View full text |Cite
|
Sign up to set email alerts
|

Unusual cause of acute scrotum in children: a case report

Abstract: A 13-year-old boy was presented in the pediatric emergency with a 2-week history of swelling of the right scrotal contents of simple evolution, which was worsened by the appearance of an acute scrotal pain 48 h prior to his consultation. The doppler ultrasound and computed tomography (CT) scan revealed an incarceration of the omentum in an inguinal hernia. Acute scrotal pain and swelling is a common reason for surgical consultation in the emergency department of children. However, omentum is a rare content of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The omentum has the potential to become irreducible, 8,23 and reports have documented a 4-year-old boy with omental infarction 9 and a 13-year-old boy with acute scrotum due to the omental infarction. 24 Furthermore, Kapisiz et al 25 reported 10 cases of omental incarceration with scrotal hydrocele. Although the incidence of irreducible IH with incarcerated omentum was extremely rare (0.7%) in the present study, omental incarceration should be included in the differential diagnosis and subsequent steps in the evaluation of acute abdomen/scrotum in older children with irreducible inguinal/scrotal mass.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The omentum has the potential to become irreducible, 8,23 and reports have documented a 4-year-old boy with omental infarction 9 and a 13-year-old boy with acute scrotum due to the omental infarction. 24 Furthermore, Kapisiz et al 25 reported 10 cases of omental incarceration with scrotal hydrocele. Although the incidence of irreducible IH with incarcerated omentum was extremely rare (0.7%) in the present study, omental incarceration should be included in the differential diagnosis and subsequent steps in the evaluation of acute abdomen/scrotum in older children with irreducible inguinal/scrotal mass.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, one male patient with herniated omentum required an emergency operation after the failure of attempts at manual reduction. The omentum has the potential to become irreducible, 8,23 and reports have documented a 4‐year‐old boy with omental infarction 9 and a 13‐year‐old boy with acute scrotum due to the omental infarction 24 . Furthermore, Kapisiz et al 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Generalmente las lesiones se producen al comprimirse los testículos contra el hueso púbico lo que provoca ruptura testicular en los casos severos y hematocele doloroso. (18)(19)(20)(21) Para llegar al diagnóstico es necesario que exista el antecedente del trauma y las manifestaciones clínicas como dolor y edema escrotal, que en ocasiones impiden la palpación del testículo. (22) Para confirmar el diagnóstico y la viabilidad del teste se debe realizar la ecografía Doppler y, en los casos dudosos o en los que hay gran aumento de volumen que causa incomodidad al paciente, es necesaria la exploración quirúrgica mediante escrototomía.…”
Section: Traumatismo Escrotalunclassified